Cytotoxic Effect of Kigelia Africana Plant Extracts on Liver Cancer Cells - M. S. Rashid, Faheem Hadi, Zoya Muzaffar, H. M. Asif, Naveed Akhtar, Memoona Zahra, . Maqbool, L. Sumreen, T. Shamim, A. Malik (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Various medicinal plants have much efficacious value as treatment of many fatal conditions including cancer. Kigelia africana has known therapeutic efficacy in different ailments and has been used as traditional medicine since ages. Aim: To evaluate anticancer property of any drug or plant extract including HepG2 cell line. Methodology: Anticancer activity of n-hexane and ethanolic extracts of Kigelia africana was checked. IC50 was evaluated via MTT assay, crystal violet assay was performed to check the viability of cells and trypan blue assay to count dead cells. Furthermore, muse analysis was performed using count and viability kit to count total living as well non-living cells. Results: Cancer cells of HepG2 cell line showed reduced viability and proliferation with increased apoptosis when treated with Kigelia extracts. Conclusion: Many drugs have been proved as anticancer but with severe side effects. Thus, phytoextracts have been tested in this study to evaluate their anti-cancer activity so minimize the side effect. Kigelia africana extracts were found to be effective against liver cancer cells. Keyword: Kigelia africana, HepG2, MTT, liver cancer, anticancer drug, plant based drugs.